(untitled) (Annals of Medical Research, 2023)
We examined the patients with hyperinsulinemic hypoglycemia who were performed non-invasive imaging techniques with doubtful or failed results. We compared the performances of the Selective Arterial Calcium Stimulation Test (SACST) and non-invasive imaging techniques. Eight patients with hyperinsulinemic hypoglycemia, performed SACST after evaluating with imaging modalities were examined retrospectively. Three patients were diagnosed with Non-Insulinoma Pancreatogenous Hypoglycemia Syndrome (NIPHS), 4 with insulinoma, and 1 with autoimmune hypoglycemia after SACST. While the concordance between the SACST and surgery-proven pathology for insulinoma was 50% (2/4), the accuracy in the localization of insulinoma was 25%. Although SACST does not have high concordance with surgery-proven pathology and accuracy in the localization of insulinoma, it may be preferred in the differential diagnosis of hyperinsulinemic hypoglycemia in medical centers where other imaging techniques are not available, or in cases where other imaging methods obtain suspicious/inadequate diagnosis.